Examining the Link Between English Proficiency and Academic Performance Among EFL Undergraduate Students - Isma, Adi; Amrang, Amrang; Ridwan, Ridwan; Rusdiah, Rusdiah (Yayasan Cendekiawan Indonesia Timur, 2025)
English language proficiency plays a vital role in supporting students’ academic performance, especially in higher education settings where English is both the subject of study and a medium for learning. This study aimed to examine the relationship between English proficiency and academic performance among undergraduate students in the English Education Department at Universitas Sulawesi Barat, Indonesia. A quantitative correlational research design was employed, involving 90 students whose English proficiency was measured using the English Proficiency Test for Internal Control (EPTIC), while academic performance was represented by their Grade Point Average (GPA). Data analysis using Pearson correlation revealed a strong and statistically significant positive relationship (r = 0.664, p < 0.001) between English proficiency and GPA. Linear regression analysis further indicated that English proficiency predicted 44.1% of the variance in academic performance. These findings highlight the importance of English proficiency as a predictor of students’ academic success. The results also support the use of institutional language assessments like EPTIC for evaluating academic readiness. It is recommended that higher education institutions provide structured language support programs to enhance student learning outcomes. Future studies should investigate the contributions of individual language skills and other influencing factors.